Urban design for an urban century : shaping more livable, equitable, and resilient cities - Brown, Lance Jay, 1943-; Dixon, David, 1947 July 17-; Gillham, Oliver (New Jersey: Wiley, 2013)
"This book offers a comprehensive introduction to urban design, from a historical overview and basic principles to practical design concepts and strategies. It discusses the demographic, environmental, economic, and social issues that influence the decision-making and implementation processes of urban design. The Second Edition has been fully revised to include thorough coverage of sustainability issues and to integrate new case studies into the core concepts discussed. Ancillary materials, including PowerPoint slides, sample questions and projects, and bonus case studies, help to enrich understanding of this topic"--
"The Second Edition has been fully revised to include thorough coverage of sustainability issues and to integrate new case studies into the core concepts discussed. Ancillary materials, including PowerPoint slides, sample questions and projects, and bonus case studies, help to enrich understanding of this topic"--
Roots of Western Urban Form : Centralization -- Decentralization : The Rise and Decline of Industrial Cities -- Recentralization : The Forces Shaping 21st-Century Urbanism -- Recentralization : 21st-century Urbanism Takes Shape.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: City planning -- Social aspects; Architecture -- Human factors; ARCHITECTURE / Urban & Land Use Planning